Granice dopuszczalnej optymalizacji podatkowej z udziałem kościelnych osób prawnych. Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 16 stycznia 2025 r., II FSK 501/22 - Zawiślak, Michał (PRAWO i WIĘŹ, 2025)
The subject of this paper is an analysis of the relevance of tax law principles to the proper application of the income tax exemption of income of a church legal entity for religiously useful purposes. The key question is the extent to which the influence of the linguistic interpretation of tax laws on the activities of church legal entities reaches. The issue under discussion has not received commentary and has not been the subject of scholarly reflection. The article also addresses the problem of limiting aggressive tax optimization involving church legal entities. The article points out the need to change the system of tax reliefs and preferences provided for religious associations.